The HR-CS-GF-AAS determination and preconcentration of palladium in contaminated urban areas, especially in lichens - Komendova, Renata (Environmental pollution (1987), 2020)
The increasing content of platinum group metal particles emitted into the environment by car traffic is gradually attracting the attention of the scientific community. However, the methods for the determination of platinum group metals in environmental matrices are either costly or suffer from low sensitivity. To facilitate the use of less sensitive, but significantly cheaper, devices, the preconcentration of platinum group metals is employed. For platinum, a multitude of preconcentration approaches have been published. On the contrary, the preconcentration approaches for palladium are still rare. In this work, the development, optimization, and testing of a new approach is described; it is based on a preconcentration of palladium on octadecyl modified silica gel together with the complexing agent dimethylglyoxime, and it is then analyzed with the high-resolution continuum-source atomic absorption spectrometry. For comparison, a newly developed sorbent, QuadraSil™ TA, with a high affinity for platinum group metals was also tested. The preconcentraiton approach was tested on the lichen Hypogymnia physodes, which served as a bioindicator of palladium emissions. The case study site was a mid-sized city in central Europe: Brno, Czech Republic. The dry "bag" monitoring technique was used to collect the palladium near roads with a large span of traffic density. The developed analytical approach confirmed an increasing concentration of palladium with increasing exposure time and intensity of the traffic. Consequently, a simple relationship between the amount of bioaccumulated palladium and traffic density was established.
Keywords: silikagel; Environmental Pollutants; monitorování životního prostředí; látky znečišťující životní prostředí; Environmental Monitoring; Lichens; lišejníky; Czech Republic; spektrofotometrie atomová; platina; Palladium; Silica Gel; Platinum; Spectrophotometry, Atomic; palladium; Cities; velkoměsta; Česká republika